(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: As sustainability is quickly becoming a predominant concept at the heart of the 21stcentury living and thinking, as well as planning for the near future, it has become obvious that financial viability is one of its core determinants. The aim of this paper has been to study the prospects of greater implementation of green infrastructure (GI) and especially green roofs (GR) in Croatia. Methodology: Theoretical framework is based on the relevant literature review, which has been conducted using qualitative methods of analysis, synthesis, comparison, induction and deduction. The empirical part of the study has been conducted as a survey amongst the civil engineering students, using questionnaire as the survey instrument. Results: The theoretical part of the research identified the relevance of costs in GI implementation and its social and economic effects, circularity principles and EU funding options. Empirical findings indicate that the majority of Millennials from the sample find the implementation of GI to be financially demanding. Moreover, they are largely unaware of the availability of EU funding for such purpose and find the frugality aspect of green roof implementation very important. Conclusion: It is acknowledged that financial viability is inevitable when considering the implementation of GI. The level of environmental awareness among Croatian Millennials is satisfactory. However, considering they were not sufficiently aware of the EU funding available for this purpose, there is a need to raise awareness among this population segment, as they are future decision-makers.